2019
DOI: 10.1177/1010539519834735
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of E-Cigarette Use Among Adults in Malaysia

Abstract: Electronic cigarettes (e-cigarettes) are a new method for the consumption of nicotine. A nationwide survey among 4288 Malaysian adults was conducted in 2016 to measure the prevalence and to describe the population characteristics of e-cigarette users. A complex sampling design was used, and data were collected using a face-to-face questionnaire. The overall prevalence of current, ever, former, and dual users of e-cigarettes in Malaysia were 3.2% (95% confidence interval [CI] = 2.5-4.1), 11.9% (95% CI = 10.5-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…That finding is consistent with Jamal's study, which found the odds of being a male smoker compared with a female smoker were higher (17.5% of men and 13.5% of women). 25 E-cigarette use is much higher in adolescents compared with adults. A study in Malaysian adults found that 9.5% had ever used e-cigarettes 9.5% compared with 16.6% of adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That finding is consistent with Jamal's study, which found the odds of being a male smoker compared with a female smoker were higher (17.5% of men and 13.5% of women). 25 E-cigarette use is much higher in adolescents compared with adults. A study in Malaysian adults found that 9.5% had ever used e-cigarettes 9.5% compared with 16.6% of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…That finding is consistent with Jamal’s study, which found the odds of being a male smoker compared with a female smoker were higher (17.5% of men and 13.5% of women). 25…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of e-cigarette use among adults is considerably low in Asia, from merely 0.02% in India and 3% in Taiwan to 11.9% in Malaysia 5 - 7 . The low figure might be attributed to the limited adoption of e-cigarette use by the general population; e-cigarette use in Asian countries was found exclusively among current or former cigarette smokers and people with high socioeconomic status 5 , 6 . However, e-cigarette use was higher among younger age groups, from 2 to 5 times higher in India and Taiwan, respectively, which highlights the challenges that ENDS/ENNDS pose to tobacco control 5 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this restriction, it is estimated that over 600 000 adults in Malaysia vape, with 3.2% of adults reporting current use. 1…”
mentioning
confidence: 99%
“…The results show that a substantial minority of the Malaysian population, particularly young men who smoke, use vaping products. 1 There has also been experimentation among adolescents, with recent use strongly associated with being a male who also smokes. 13 While these surveys indicate the need for ongoing close monitoring of vaping prevalence in Malaysia, they also demonstrate the continued high prevalence of smoking among Malaysian men.…”
mentioning
confidence: 99%